2021
DOI: 10.1002/eat.23466
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between patterns of weight‐related self‐monitoring and eating disorder symptomology among undergraduate and graduate students

Abstract: Objective To characterize patterns of weight‐related self‐monitoring (WRSM) among US undergraduate and graduate students and examine associations between identified patterns of WRSM and eating disorder symptomology. Method Undergraduate and graduate students from 12 US colleges and universities (N = 10,010) reported the frequency with which they use WRSM, including self‐weighing and dietary self‐monitoring. Eating disorder symptomology was assessed using the Eating Disorder Examination Questionnaire. Gender‐sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This practice has been associated with higher body dissatisfaction rates [ 53 ] and disordered eating [ 54 ]. It has been reported that young women engage in this behavior more frequently than young men [ 55 ]. Posting personal photos on SNSs seems to make it easier for women to compare their appearance with that of others [ 22 , 24 ] as individuals tend to share photos of themselves in which they are aesthetically attractive and without any imperfections [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…This practice has been associated with higher body dissatisfaction rates [ 53 ] and disordered eating [ 54 ]. It has been reported that young women engage in this behavior more frequently than young men [ 55 ]. Posting personal photos on SNSs seems to make it easier for women to compare their appearance with that of others [ 22 , 24 ] as individuals tend to share photos of themselves in which they are aesthetically attractive and without any imperfections [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…One significant concern with self-monitoring body dimensions is the potential for developing disordered eating habits from focusing on body image. 73 Subsequently, participants should be reminded that, unlike weight, body composition requires more time to assess changes and should not be monitored daily but rather monthly or longer depending on the health of the individual. Education ensures that users interpret body composition results accurately, make informed choices, and prioritize overall well-being and is therefore a vital component of using at-home testing apps effectively.…”
Section: Challenges and Limitations To At-home Testingmentioning
confidence: 99%
“…Furthermore, empowering patients/clients with the knowledge to make behavioral changes when needed can increase the usefulness of these apps. One significant concern with self‐monitoring body dimensions is the potential for developing disordered eating habits from focusing on body image 73 . Subsequently, participants should be reminded that, unlike weight, body composition requires more time to assess changes and should not be monitored daily but rather monthly or longer depending on the health of the individual.…”
Section: Challenges and Limitations To At‐home Testingmentioning
confidence: 99%
“…At the same time, women are expected to engage in regular and rigorous exercise, behaviours positioned within popular culture as healthy and necessary to prevent their bodies from becoming fat and 'out of control' [1,8]. Normalisation of these behaviours within the media can be problematic for women, encouraging disordered eating, unhealthy exercise behaviours and body dissatisfaction [9][10][11]. Body dissatisfaction and failure to meet these ideals has negative implications for mental health, associated with increased risk of depression and low self-esteem [12][13][14].…”
Section: Introductionmentioning
confidence: 99%